PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PUSKESMAS - ADHI SATRIYAWAN; SUKRISPIYANTO (AKADEMIKA, 2023)
The purpose of this study was to determine and analyze the effect of the work environment, workload and organizational culture on the performance of Pamotan Health Center employees. This type of research is descriptive. The type of data used is primary data. Primary data collection was carried out through questionnaires distributed to Pamotan Health Center staff. Methods of data analysis using descriptive quantitative method, namely with multiple linear regression analysis. The population in this study were Pamotan Health Center employees, totaling 56 people. The sample in this study used the saturated sample method, with a total sample of 56 people.The results obtained from this study indicate that simultaneously work environment, workload and organizational culture have a significant effect on the performance of Pamotan Health Center employees, and partially show work environment, workload and organizational culture have a positive and significant effect on the performance of Pamotan Health Center employees.